The Relationship Between Anxiety Levels and Pre-operative Sleep Quality Disorders for Spinal Anesthesia Patients - Pratama, Ilham; Susanto, Amin; Budi, Martyarini (Java Nursing Journal, 2024)
Background: According to data, the number of surgery patients has increased significantly over time. All hospitals worldwide recorded 140 million patients in 2017, 148 million in 2019, and 1.2 million in Indonesia. Surgery might threaten a person's body, integrity, or life and generate anxiety. Patients can be anxious before surgery under anaesthesia. Chronic anxiety can create stress and sleep difficulties. People with sleep issues are young adults. Sleep disorders are conditions that cause discomfort or interfere with a desirable lifestyle due to alterations in rest patterns. Purpose: Understanding how worry affects preoperative sleep quality in spinal anaesthesia patients at Hj. Anna Lasmanah Banjarnegara Hospital. Methods: This type of research is descriptive correlation using a cross sectional design by distributing questionnaires of anxiety level (APAIS) and sleep quality (AIS). Findings: the findings regarding the anxiety levels of the 65 participants indicated that among the total of 65 respondents, 23 individuals (or 35.4%) reported having moderate anxiety. Furthermore, in terms of sleep quality disorders, moderate insomnia was reported by most respondents, comprising 28 individuals (43.1%). The significance value of p = 0.000 (<0.05) obtained from the Spearman's Rho correlation test indicates that anxiety levels and sleep quality disorders are significantly associated in preoperative spinal anaesthesia patients. Conclusion: There is a strong relationship between anxiety level and preoperative sleep quality disorders in spinal anesthesia patients.